2011
DOI: 10.1089/scd.2010.0175
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of CD14 Expression Levels in Putative Mesenchymal Progenitor Cells Isolated from Equine Bone Marrow

Abstract: A long-term goal of mesenchymal progenitor cell (MPC) research is to identify cell-surface markers to facilitate MPC isolation. One reported MPC feature in humans and other species is lack of CD14 (lipopolysaccharide receptor) expression. The aim of this study was to evaluate CD14 as an MPC sorting marker. Our hypothesis was that cells negatively selected by CD14 expression would enrich MPC colony formation compared with unsorted and CD14-positive fractions. After validation of reagents, bone marrow aspirate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…However, results of a recent study demonstrate that CD14 might not be an appropriate negative MSC marker, as selection of CD14 positive equine bone marrow derived mesenchymal progenitor cells led to higher yields of adherent cells than selection of their CD14 negative counterparts. Furthermore, in this study, high CD14 mean fluorescence intensity was detected in early cell cultures, which decreased over time but then remained constant at a lower level (83). The absence of other negative markers such as CD34 and CD45 seems to be confirmed (75–78).…”
Section: In Vitro Characterization Of Equine Stem Cellsmentioning
confidence: 51%
“…However, results of a recent study demonstrate that CD14 might not be an appropriate negative MSC marker, as selection of CD14 positive equine bone marrow derived mesenchymal progenitor cells led to higher yields of adherent cells than selection of their CD14 negative counterparts. Furthermore, in this study, high CD14 mean fluorescence intensity was detected in early cell cultures, which decreased over time but then remained constant at a lower level (83). The absence of other negative markers such as CD34 and CD45 seems to be confirmed (75–78).…”
Section: In Vitro Characterization Of Equine Stem Cellsmentioning
confidence: 51%
“…The lower expression of CD90 and CD105 than expected, on the basis of ISCT stated [15], could be determined by multiple factors. It has been demonstrated that certain cell surface markers can be trypsin labile, which causes a functional impairment or even their removal [33]. Recently, Paebst et al [18] reported that the CD90 expression on equine cells is very sensitive to the action of enzymes used for detaching cells, including trypsin and accutase.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been stated by the International Society of Cellular Therapy that mesenchymal stromal cells should be >95% positive for CD73 and CD105, several studies report a lower or even no expression for human, canine or equine mesenchymal stromal cells . Furthermore, it has been demonstrated that certain cell surface markers can be trypsin‐labile, which causes a functional impairment or even their removal . If this applies to CD73 and CD105, mesenchymal stromal cells would appear negative for markers upon immunophenotyping.…”
Section: Discussionmentioning
confidence: 99%